Sistem Booking Jadwal Kursus Mengemudi Dengan Menggunakan Algoritma First Come First Serve (Studi Kasus Wiwit Kursus Mengemudi) - Soleh , Rahmat; Sucipto , Hadi; Augusta Jannatul Firdaus , Reza (Inovate, 2023)
Schedule is the most important factor in supporting activities in various ways, especially in teaching and learning activities. In managing the driving course wiwit schedule it is done manually and recorded in a book based on an agreement between the admin and the students. This will cause problems if orders are made simultaneously there will be a conflict. The solution to these problems can be overcome by making a schedule booking system for driving courses. This research method uses the First Come First Serve algorithm to solve problems in the driving course schedule booking system. algorithm that has a characteristic which prioritizes processes that have been submitted in advance, namely those that arrive first will be served or processed first. The results of the research produce products in the form of web-based applications. The purpose of using this algorithm so that each processqueue executed fairly in the sense of sequentially without any priority. So that each process will run sequentially. From the results of this algorithm produces a sequence queue based on who has submitted first then it will get queue of front. Keywords : Booking System, Website, First Come First Serve.